2002
DOI: 10.4049/jimmunol.168.3.1356
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Tumor Initiation and Metastasis in TNF-Related Apoptosis-Inducing Ligand-Deficient Mice

Abstract: We have previously implicated TNF-related apoptosis-inducing ligand (TRAIL) in innate immune surveillance against tumor development. In this study, we describe the use of TRAIL gene-targeted mice to demonstrate the key role of TRAIL in suppressing tumor initiation and metastasis. Liver and spleen mononuclear cells from TRAIL gene-targeted mice were devoid of TRAIL expression and TRAIL-mediated cytotoxicity. TRAIL gene-targeted mice were more susceptible to experimental and spontaneous tumor metastasis, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
440
1
8

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 572 publications
(460 citation statements)
references
References 24 publications
11
440
1
8
Order By: Relevance
“…mDR5-knockout mice are viable and develop normally (Diehl et al, 2004). Similarly, Apo2L/TRAIL-knockout mice do not display any overt developmental defects, indicating that, as in zebrafish, Apo2L/TRAIL signaling is not essential for normal mouse embryonic development (Cretney et al, 2002). Apo2L/TRAIL is expressed specifically on the surface of natural killer cells, cytotoxic T cells, macrophages and dendritic cells, and transcription of its mRNA can be induced by type I Apoptosis signaling by Apo2L/TRAIL F Gonzalvez and A Ashkenazi interferons (Almasan and Ashkenazi, 2003).…”
Section: Drsmentioning
confidence: 96%
See 3 more Smart Citations
“…mDR5-knockout mice are viable and develop normally (Diehl et al, 2004). Similarly, Apo2L/TRAIL-knockout mice do not display any overt developmental defects, indicating that, as in zebrafish, Apo2L/TRAIL signaling is not essential for normal mouse embryonic development (Cretney et al, 2002). Apo2L/TRAIL is expressed specifically on the surface of natural killer cells, cytotoxic T cells, macrophages and dendritic cells, and transcription of its mRNA can be induced by type I Apoptosis signaling by Apo2L/TRAIL F Gonzalvez and A Ashkenazi interferons (Almasan and Ashkenazi, 2003).…”
Section: Drsmentioning
confidence: 96%
“…In mice, either antibody blockade or genetic ablation of Apo2L/TRAIL supports a role for this ligand in the suppression of experimental and spontaneous tumor metastasis in vivo (Takeda et al, 2001;Cretney et al, 2002). Recently, comparison of geneexpression profiles in a panel of 368 human breast tumor samples revealed that downregulation of Apo2L/ TRAIL correlates with breast cancer metastasis to the brain (Bos et al, 2009).…”
Section: Drsmentioning
confidence: 97%
See 2 more Smart Citations
“…26 Interestingly, however, while Fas (lpr) and FasL (gld) mutant mice show clear symptoms of uncontrolled immune cell activation, defects in cellular homeostasis, reduced apoptosis and development of autoimmune disease, 27 none of these signs is obvious in the TRAIL-deficient mouse, at least not at the first glance. 28,29 Yet, a more detailed analysis revealed that lack of TRAIL predisposes to increased susceptibility to the development of autoimmune diseases. For example, C57BL/6 mice are usually resistant to collagen-induced arthritis but develop severe disease in the absence of TRAIL expression.…”
Section: Role Of Trail In Immune Regulation Immunopathologies and Aumentioning
confidence: 99%